5s+4t-2s-(-3t)=

Simple and best practice solution for 5s+4t-2s-(-3t)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5s+4t-2s-(-3t)= equation:


Simplifying
5s + 4t + -2s + -1(-3t) = 0

Remove parenthesis around (-3t)
5s + 4t + -2s + -1 * -3t = 0

Multiply -1 * -3
5s + 4t + -2s + 3t = 0

Reorder the terms:
5s + -2s + 4t + 3t = 0

Combine like terms: 5s + -2s = 3s
3s + 4t + 3t = 0

Combine like terms: 4t + 3t = 7t
3s + 7t = 0

Solving
3s + 7t = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-7t' to each side of the equation.
3s + 7t + -7t = 0 + -7t

Combine like terms: 7t + -7t = 0
3s + 0 = 0 + -7t
3s = 0 + -7t
Remove the zero:
3s = -7t

Divide each side by '3'.
s = -2.333333333t

Simplifying
s = -2.333333333t

See similar equations:

| 4.75d=.07d^3/2 | | n-24=8 | | 99g-1=98 | | 22=29x+4 | | -5x-2=Y | | ytjg+7981=12345 | | 5x-60+8x-120=x-60 | | ytjg+7981=12345g | | 2x+3x+5=37 | | 2x-5(1-x)=1-3(1-2x) | | y=-2(x-5)(x-9) | | 7x+1+8x= | | 5x-6=3(2x-1)+8 | | 5x+196=13x-12 | | t(y)=36(10)-045y | | 8a+6-11=11 | | 3x-12=x-4 | | 70=6+x | | 15y+3=-36-18 | | ln(t+8)+ln(t-1)-1=0 | | 56-4x=5x+24 | | 1+2(7x-7)=-14 | | 12x=-47+107 | | 6-10x=66-31x | | 2m+9=29 | | 8x-30=-6(x-9) | | -7u-2=5u^2 | | 5x=36.2 | | 2+4=x-7 | | 3w^2-11w=4 | | 2k=101 | | 3(c-9)=-6 |

Equations solver categories